(untitled) (Journal of Transport System Engineering, 2024)
Polyalphaolefin (PAO) lubricants have long been a staple in the aviation industry, prized for their exceptional friction-reduction properties in high-temperature environments. However, as the industry embraces electrification to decarbonise passenger planes, the demand for suitable lubricants to accommodate the extreme working conditions of electric motors has surged. Understanding how these lubricants perform under electrical conditions becomes crucial, particularly by delving into the frictional characteristics when exposed to electrical current. This study explores the frictional behaviour of PAO4, a specific type of PAO lubricant when subjected to electrical working conditions. It is to conclude that the frictional performance of PAO4 decreases subject to electrical current discharge, with the friction increasing around 30% with an additional temperature increment of 15%. Thus, the investigation aims to understand the interplay between friction and electrical current within the evolving aviation industry.